2021
DOI: 10.21037/atm-20-4865
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of spatial patterns at the network-level in facial synkinesis: an independent component and connectome analysis

Abstract: Background: The treatment of post-facial palsy synkinesis (PFPS) remains inadequate. Previous studies have confirmed that brain plasticity is involved in the process of functional restoration. Isolated activation has been well studied, however, the brain works as an integrity of several isolated regions. This study aimed to assess the alteration of the brain network topology with overall and local characteristics of information dissemination. Understanding the neural mechanisms of PFPS could help to improve th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The images were first dimensionally reduced using principal component analysis (PCA) and then temporally concatenated and reduced using an expectation–maximization algorithm at the group level to extract 40 spatial components. Furthermore, the infomax ICA algorithm was performed in ICASSO for 100 repetitions to verify its robustness ( 38 ).…”
Section: Methodsmentioning
confidence: 99%
“…The images were first dimensionally reduced using principal component analysis (PCA) and then temporally concatenated and reduced using an expectation–maximization algorithm at the group level to extract 40 spatial components. Furthermore, the infomax ICA algorithm was performed in ICASSO for 100 repetitions to verify its robustness ( 38 ).…”
Section: Methodsmentioning
confidence: 99%
“…In our clinical observations, patients with homogeneous etiologies show high heterogeneity in asymmetry outcomes ( Chen et al, 2017 ; Ma et al, 2022 ). A recent study has demonstrated that facial nerve lesions induce widespread cerebral plasticity, including changes in cortical reorganization and functional connectivity, which correlate with clinical severity ( Klingner et al, 2012 ; Song et al, 2017 ; Ma et al, 2021a , b ). There is also evidence to suggest that cerebral plasticity contributes to facial muscle dysfunction ( He et al, 2014 ; Xiao et al, 2015 ; Ma et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…3 However, newer findings such as reduced intrinsic connectivity in subnetworks of the central nervous system highlight that the full extent of the pathophysiology may not yet be completely understood. 4 Synkinetic movements have an undeniable aesthetic impact and can, in severe cases, be quite painful. Overall, PPFS can be socially debilitating, limit interpersonal interactions, and has a significant impact on the quality of life of affected patients.…”
mentioning
confidence: 99%